Hubungan Pengetahuan Gizi Dan Kebiasaan Konsumsi Junk Food Dengan Status Gizi Pada Siswa Kelas XI SMK Ketintang Surabaya - Devi Sekar Wangi (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Junk food is food that is easily found in urban areas. The practical urban lifestyle allows someone to prefer junk food. Lack of nutritional knowledge influences the habit of consuming food without paying attention to its nutritional content just because it tastes good. This can affect nutritional status. This research aims to: (1) determine the relationship between nutritional knowledge and nutritional status in class XI students at Ketintang Vocational School, Surabaya. (2) determine the relationship between junk food consumption habits and nutritional status in class XI students at Ketintang Vocational School, Surabaya. This research is an analytical observational study with a cross sectional design. The research location was carried out at Ketintang Vocational School, Surabaya, with 91 class XI student respondents taken using a simple random sampling technique. Data collection was carried out by filling out a questionnaire. Questionnaires were used to obtain data on respondents' identities, level of nutritional knowledge and food frequency questionnaires to determine respondents' junk food consumption habits. To determine the nutritional status of respondents, the BMI/U index is obtained by weighing their body weight and measuring their height directly. The research instrument was adopted from previous research and has been validated by expert lecturers in the field. The data analysis technique used is the chi square test.The results of the research show: (1) the results of statistical tests on nutritional knowledge with the nutritional status of students, namely sig 0.394 > 0.05, which indicates there is no significant relationship between the two variables, (2) the results of statistical tests on junk food consumption habits with nutritional status sig 0.001 < 0.05 which indicates a significant relationship between the two variables. Based on this, it can be concluded that there is no relationship between nutritional knowledge and students' nutritional status, but there is a relationship between junk food consumption habits and nutritional status in class XI students at Ketintang Vocational School, Surabaya.